Analysis of Coping Strategies with the Anxiety of Pasuruan Regency IBI Implementing Midwives in the New Normal Era - Eni Wahyuni; Endah Pujiati (Journal for Research in Public Health, 2022)
The high death rate of health workers who died due to COVID-19. Midwives are at the forefront of midwifery services during the Covid-19 pandemic and must continue to provide midwifery services. Apart from that, the high maternal mortality rate causes anxiety among service providers, especially midwives. The aim of writing this research is to find out the relationship between coping strategies and the anxiety level of IBI midwives in Pasuruan Regency in the new normal era. Method This research uses a correlative descriptive research design, namely research to examine the relationship between two variables in a situation or group of objects with a cross sectional approach.. The research was carried out at IBI Pasuruan Regency Branch. Sampling technique uses random sampling of 133 midwives. The analysis used uses Chi-square The research results showed that the majority chose the PFC coping strategy as many as 100 respondents (75.2%). Respondents experienced emergency mild as many as 65 respondents (48.9%) and respondents with moderate anxiety amounting to 54 respondents (40.6%). Analysis results The data was then tested using statistical tests Chi-Square. The results obtained were p (0.000) < 0.05, meaning that there is a relationship Coping strategies for anxiety by IBI Managing Midwives in Pasuruan Regency in the New Normal Era. It is hoped that the Indonesian Midwives Association organization will pay more attention to the psychological health of midwives, because midwives are the front guard in providing health services for mothers and babies in the current Covid pandemic era. Apart from providing support, the availability of facilities and infrastructure, especially PPE for midwives, is being given more attention.